Political Branding of Prabowo Subianto in Instagram During the Presidential Campaign in 2024 - Wijanarko, Totok Ony; Agusta, Yori Dwi Bari; Hutapea, Edison Bonartua; Mufti, Zulfikar; Putri, Amanda Kanary (Journal of Digital Marketing and Communication, 2025)
The campaign period in the 2024 presidential election was crucial for the three presidential candidate pairs (Anies-Muhaimin, Prabowo-Gibran, and Ganjar-Mahfud) to develop and implement their political communication strategies. Branding was a key aspect of political communication that needed to be considered. One of the more interesting aspects was the branding of Prabowo as a candidate participating in the presidential election for the fourth time, now showcasing a different character. This research was conducted to analyze Prabowo's political branding through social media during the 2024 presidential election campaign. The focus of the research was to describe Prabowo's political branding by categorizing it into three parts: house brands, platform brands, and product brands, in accordance with the brand hierarchy theory from Cosgrove. The method used for the research was qualitative content analysis. Data and information were obtained through an analysis of the content on Prabowo's Instagram account and interviews with three sources related to the research topic. The results of the study showed that the house brand of Prabowo's political branding through social media during the 2024 presidential election campaign was "Prabowo Subianto 2024." Five brand platforms were identified: Humanism, Continuity, Bersama Indonesia Maju (Together with Onward Indonesia), Militarism, and Free Lunch. Furthermore, the product brand identified was Aksi Gemoy, which was part of Humanism.